Features of moral regulation of relations between participants of educational process in pre-school (Pedagogy of Higher and Secondary Education, 2013)
Fedorovych A. V. Features of moral regulation of relations between participants of educational process in pre-school.In the article is exemined the role of ethics in professional activity of preschool teacher; basic moral principles of pedagogical co-operation(optimism; civility; humanism; legality; justice; gender equality; independence; mutual respect, trust, goodwill, tactfulness, and other) is underline; the value of internal acceptance of moral requirements of educator.
Keywords: preschool teacher; educator; ethics of mutual relations; pedagogical ethics; ethic principles; moral quality